Using the lineage determinants Olig2 and Sox10 to explore transcriptional regulation of oligodendrocyte development - Sock, Elisabeth; Wegner, Michael (Developmental Neurobiology, 2021)
The transcription factors Olig2 and Sox10 jointly define oligodendroglial identity. Because of their continuous presence during development and in the differentiated state they shape the oligodendroglial regulatory network at all times. In this review, we exploit their eminent role and omnipresence to elaborate the central principles that organize the gene regulatory network in oligodendrocytes in such a way that it preserves its identity, but at the same time allows defined and stimulus-dependent changes that result in an ordered lineage progression, differentiation, and myelination. For this purpose, we outline the multiple functional and physical interactions and intricate cross-regulatory relationships with other transcription factors, such as Hes5, Id, and SoxD proteins, in oligodendrocyte precursors and Tcf7l2, Sip1, Nkx2.2, Zfp24, and Myrf during differentiation and myelination, and interpret them in the context of the regulatory network.
CRIS-Team Scopus Importer:2021-09-24
Keywords: olig; oligodendrocyte; regulatory network; Sox; transcriptional regulation